No more violence against women. (Journal of Parents and Teachers, 2014)
This article offers a series of figures on women who, in one way or another, suffer violence. However, many others are afraid to report this harassment, so these numbers are just the tip of the iceberg.
Keywords: Figures; women; mistreatment; violence.